PEMBERDAYAAN MASYARAKAT DESA MUARA BAKTI MELALUI KERJA BAKTI, PENGEMBANGAN UMKM DAN FASILITAS LINGKUNGAN DESA - Salwa Rafi’Ah Imanina; Erlandi Putra Triadira, Fitriyani Suci Supari, Senja Al-Fitrah, Aulia Nabilla, Lhivia Nur’aini Putri (JOURNAL OF COMMUNITY DEDICATION, 2026)
Community Service Learning (KKN) is a learning program that integrates the implementation of the Tri Dharma of Higher Education with learning and working experiences in the community, with the aim of empowering the community. We, the KKN Group 60 from Bhayangkara University of Greater Jakarta, had the opportunity to conduct KKN activities in Muara Bakti Village, RT.03, by adopting the Sustainable Development Goals (SDGs). Based on observations conducted on-site, the environmental conditions in RT.03 of Muara Bakti Village still require in-depth review, particularly regarding environmental cleanliness, area planning, and local economic opportunities such as those for small and medium-sized enterprises (SMEs) that have not yet been fully utilized. Therefore, we will implement four main programs: installing a village gate, organizing a community service event, putting up SME banners, and installing a sign for the mosque. Using a descriptive method and a participatory approach, information was collected through direct observation, interviews, and documentation, drawing on primary data from the field and secondary data from various academic sources. Based on the results, these program activities have provided positive benefits for local residents: the construction of the village gate and the installation of the mosque sign have strengthened the village’s identity; the community service activities and cleanup of the mosque area have contributed to a cleaner environment; and the installation of promotional banners for SMEs has helped increase business exposure.